Impact of CytoSorb® on interleukin-6 in cardiac surgery - Geisler, Daniela; Arleth, Noemi; Grabenwöger, Johannes; Arnold, Zsuzsanna; Aschacher, Thomas; Winkler, Bernhard; Mach, Markus; Grabenwöger, Martin (Frontiers in Cardiovascular Medicine, 2023)
Objective. Cardiac surgery is known to activate a cascade of inflammatory mediators leading to a systemic inflammatory response. Hemadsorption (HA) devices such as CytoSorb® have been postulated to mitigate an overshooting immune response, which is associated with increased morbidity and mortality, and thus improve outcome. We aimed to investigate the effect of CytoSorb® on interleukin (IL)-6 levels in patients undergoing complex cardiac surgery in comparison to a control group.Methods. A total of 56 patients (28 CytoSorb®, 28 control) undergoing acute and elective cardiac surgery between January 2020 and February 2021 at the Department of Cardiac and Vascular Surgery, Clinic Floridsdorf, Vienna, were retrospectively analyzed. The primary endpoint was the difference in IL-6 levels between the CytoSorb® and control group. Secondary endpoint was periprocedural mortality.Results. CytoSorb®, installed in the bypass circuit, had no significant effect on IL-6 levels. IL-6 peaked on the first postoperative day (HA: 775.3±838.4 vs. control: 855.5±1052.9 pg/mL, p=0.856). In total, three patients died in the HA group, none in the control (logistic regression model, p= 0.996). Patients with an increased Euroscore II of 7 or more showed a reduced IL-6 response compared to patients with an Euroscore II below 7 (178.3±63.1 pg/mL vs. 908.6± 972.6 pg/mL, p-value = 0.00306).No significant reduction of IL-6 levels or periprocedural mortality through intraoperative HA with CytoSorb® in patients undergoing cardiac surgery was observed.However, this study was able to show a reduced immunologic response in patients with a high Euroscore II. The routine application of CytoSorb® in cardiac surgery to reduce inflammatory mediators has to be scrutinized in future prospective randomized studies.